Gender Equality Practices by the teachers inside the classrooms: a comparative study between a government and a non- government primary school - Islam, J M Saiful (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Masters of Science in Early Child Development, 2021.